Combined BSA-seq and RNA-seq approaches reveal candidate genes associated with seed weight in Brassica napus - Geng, Xinxin; Yang, Fengling; Tang, Wenhua; Wang, Ying; Fu, Shan; Yu, Zichen; Cheng, Wanli; Chen, Liang; Xue, Xiaomeng (Frontiers in Plant Science, 2025)
Brassica napus, a globally significant oilseed crop of the Brassicaceae family, serves as a major source of vegetable oil and biofuel. Seed size/weight is a crucial agronomic trait that directly determines crop yield. However, the genetic mechanisms underlying seed weight in B. napus has not been fully understood. In this study, R140 with extremely low thousand-seed weight (2.6g) was crossed with Zhongshuang 11 (4.9g) to construct an F2 population. Five major genomic regions on chromosomes A06 (43.88-44.63Mb), A08 (27.63-27.68Mb), A09 (55.32-55.46Mb, 57.33-57.58Mb), and C07 (29.40-29.60Mb) were identified as candidate loci of seed weight via BSA-seq approach. A total of 204 genes were annotated within the candidate regions, including 103 non-synonymous mutant genes and 26 frameshift mutant genes identified between parental lines. Among them, 21 DEGs were screened through RNA-seq analysis of the developing seeds in both parents. However, only 8 genes exhibited mutations in their coding or upstream sequences, which were characterized as the candidate genes associated with the small seed phenotype of R140. An auxin response factor18 coding gene (BnARF18) exhibited significantly differential expression between parents. Analysis of the promoter element variations revealed that the MYC-motif, implicated in gene expression regulation, and the WUN-motif, associated with cell differentiation and proliferation control, likely serve as key regulatory motifs responsible for the differential expression levels of BnARF18 between the two parental lines. It was therefore considered to be the most likely candidate gene. In conclusion, this study provides clues for elucidating the molecular mechanism of seed weight regulation in Brassica napus.